Implementation of Guided Imagery Pain Management in Post-Caesarean Section Patients in an Effort to Reduce Pain Levels in Bandung City Hospital Area - Elisa Situmorang; Anri; Roganda Situmorang (HealthCare Nursing Journal, 2026)
The number of post-cesarean section patients worldwide increased by around 21% from 2021 to 2025, representing almost a third of all deliveries. This increase is projected to continue until 2026 to 2030, exceeding the ideal standard of around 10-15%. Caesarean section surgery has unpleasant side effects such as pain, and current treatment still focuses on pharmacological therapy and is starting to vary to non-pharmacological guided imagery therapy. This study aims to determine the effect of guided imagery pain management on post-cesarean section patients in efforts to reduce pain levels in the Bandung City Hospital area. The research method used a quasi-experimental approach with a pre-experimental design with a one-group pretest-posttest only design. The sample was 90 post-cesarean section patients. The research instrument used standard operating procedures for guided imagery therapy and a numeric rating scale. The analysis included univariate analysis with frequency distribution calculations and bivariate analysis with the Wilcoxon signed-rank test. The results of the study proved that there was an effect (p-value 0.000) of guided imagery pain management in post-cesarean section patients on efforts to reduce pain levels and the average respondent experienced a 100% reduction in pain in all post-cesarean section patients. It is recommended that guided imagery therapy as a non-pharmacological therapy can be used to reduce pain in post-cesarean section patients.